From Islamic Feminism to Radical Feminism: Roquiah Sakhawat Hossein to Taslima Nasrin - Zaman, Independent University, Bangladesh, Niaz (Asiatic: IIUM Journal of English Language and Literature, 2016)
This paper examines four women writers who have contributed through their writings and actions to the awakening of women in Bangladesh: Roquiah Sakhawat Hossein, Sufia Kamal, Jahanara Imam and Taslima Nasrin. The first three succeeded in making a space for themselves in the Bangladesh tradition and carved a special niche in Bangladesh. All three of them were writers in different genres – poetry, prose, fiction – with the last best known for her diary about 1971. While these iconic figures contributed towards women’s empowerment or people’s rights in general, Taslima Nasrin is the most radically feminist of the group. However, while her voice largely echoes in the voices of young Bangladeshi women today – often unacknowledged – she has been shunned by her own country. The paper attempts to explain why, while other women writers have also said what Taslima Nasrin has, she alone is ostracised.